Carcass characteristics of Hampshire Down and Santa Inês ram lambs under different photoperiods - Sá, José Luiz de; Siqueira, Edson Ramos de; Sá, Cristiane Otto de; Roça, Roberto de Oliveira; Fernandes, Simone (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to evaluate the effect of photoperiod and breed on carcass characteristics. Seven Hampshire Down and seven Santa Inês ram lambs were assigned to two photoperiods: 12 hours light x 12 hours dark, or short photoperiod, and to 18 hours of light x 6 hours of dark, or long photoperiod. After weaning, the lambs were housed in individual stalls. The lambs were weighed weekly until slaughter weight of 31 kg. After slaughter, the carcass and the non-carcass components were weighed. Santa Inês lambs had higher hot carcass weight than Hampshire Down and also a higher commercial dressing percentage. Santa Inês lambs had higher blood, heart, lung, kidneys and spleen weight. The Hampshire Down lambs had higher skin, feet, full stomach and full intestine weight. Santa Inês lambs had higher width hindquarters and leg length than the Hampshire Down. Santa Inês lambs had higher percentage of discovered rib and low and the Hampshire Down lambs, higher percentage of leg. Breed influences more the carcass characteristics than photoperiod.